2017
DOI: 10.1111/tbed.12736
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of hepatitis E virus in wild boar population in eastern Romania

Abstract: In industrialized countries, Hepatitis E is a recognized zoonosis, with wild boar and swine representing the main reservoirs for zoonotic genotype HEV-3 in Europe. Data related to HEV infection in wild boar population in Romania are restricted to serological surveys. Therefore, our main goal was to determine the HEV prevalence in wild boar population and to characterize HEV strains circulating in Romania. Using TaqMan real-time RT-PCR assay, we analyzed the presence of RNA HEV in 45 liver samples and five sple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Recent studies in Europe revealed molecular evidence for HEV infection in wild boar and high HEV seroprevalences [24][25][26][27][28]. The HEV disease-dynamic in wild boar is similar to domestic pigs; the infection frequency also increases with age as well as the possibility of viral chronification [29].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in Europe revealed molecular evidence for HEV infection in wild boar and high HEV seroprevalences [24][25][26][27][28]. The HEV disease-dynamic in wild boar is similar to domestic pigs; the infection frequency also increases with age as well as the possibility of viral chronification [29].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, extrahepatic sites of virus replication have been shown. HEV also efficiently replicates in the spleen, and to a lesser extent in the kidneys, lungs and lymph nodes [ 21 , 22 , 23 ]. As with pigs, a periodic shedding of the virus in the faeces of wild boars has also been observed [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis E virus is a zoonotic pathogen with pigs and wild boars serving as natural reservoirs, especially for zoonotic genotypes HEV‐3 and HEV‐4 . Considering the identification of HEV new isolations in disparate animal species, it is obvious that HEV has a broad host range including pigs, rabbits, cats, dogs, horses, rats, cows, sheep, goats and ferrets .…”
Section: Discussionmentioning
confidence: 99%